2011
DOI: 10.5937/sjecr1102075d
|View full text |Cite
|
Sign up to set email alerts
|

Oxide in hemodialysis patients

Abstract: Nitric oxide (NO) is a molecule that has an important SAŽETAK Molekul azotnog monoksida (NO) ima važnu ulogu u mnogim fi ziološkim i patološkim stanjima na šta ukazuju mnoge studije koje objašnjavaju njegovu funkciju u različitim bolestima. Bubrežne bolesti pokazuju poremeċaj aktivnosti NO koja utiče na razvoj bolesti i njenu prognozu. Cilj ove studije je da se kod pacijenata na hemodijalizi (HD) ispita povezanost NO-a sa dužinom trajanja hemodijalize i sa eritropoetinskom terapijom (rhEpo). Koncentracija NO-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Dejanova et al have shown that patients on hemodialysis have significantly higher levels of NO compared to control group subjects (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dejanova et al have shown that patients on hemodialysis have significantly higher levels of NO compared to control group subjects (4).…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that the change (increase) in the NO synthesis concentration may help to relieve some pathological changes that can be seen in uremia such as: predisposition to bleeding, well-known uremia complications and hemodialysis hypotension (3). Dejanova et al have demonstrated higher levels of NO in patients on hemodialysis than those in the control group (4). The authors believe that the increase in NO in patients on hemodialysis is caused by hemodialysis membrane and/or lack of renal excretion.…”
Section: Introductionmentioning
confidence: 99%